2017
DOI: 10.1177/1043659617747686
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Stress and Maternal–Child Interactions Among Preschool Mothers From the Philippines, Korea, and Vietnam: A Cross-Sectional, Comparative Study

Abstract: The characteristics of maternal-child interactions according to the mother's nationality may inform parent education in multicultural societies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Parenting stress may have a broad impact on parents, children, and may also impact the parent–child relationship [ 6 ]. Higher levels of parenting stress have been linked to increased depression, anxiety, and fatigue in parents [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Parenting stress may have a broad impact on parents, children, and may also impact the parent–child relationship [ 6 ]. Higher levels of parenting stress have been linked to increased depression, anxiety, and fatigue in parents [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study on the differences in parenting stress (using the Parenting Stress Index-Short Form) and childhood problem behaviors between Korean and American mothers found that Korean mothers reported a significantly higher degree of parenting stress, yet a significantly lower degree of childhood problem behaviors, than American mothers [ 27 ]. One study examining the parenting stress (using the Parenting Stress Index-Short Form) and maternal-child interactions of married immigrant mothers from the Philippines, Vietnam, and Korea found that the level of parenting stress between Korean mothers in general and disadvantaged mothers from the Philippines and Vietnam living in Korea was similar [ 28 ]. In addition, an investigation conducted by the Korea Institute of Child Care and Education [ 18 ] surveyed 300 Korean households with children under 12 years old using the European Quality of Life Survey to measure parents’ quality of life to compare the quality of life of parents from Korea with parents from nations in the EU.…”
Section: Discussionmentioning
confidence: 99%